ANALISIS PENGARUH PERSEPSI MANFAAT, PERSEPSI KEMUDAHAN, DAN KEAMANAN TERHADAP MINAT NASABAH MENGGUNAKAN MOBILE BANKING (Studi Kasus pada PT Bank Rakyat Indonesia (Persero) Tbk Kantor Cabang Semarang Pandanaran) - Margaretha Oktavia Pranoto; R. Gunawan Setianegara (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This research is motivated by the phenomenon of competition in the banking industry in increasing customers interest in using mobile banking. This research aims to analyze the perceived usefulness, perceived ease of use, and security on the interest in using mobile banking at the PT Bank Rakyat Indonesia (Persero) Tbk Branch Office Semarang Pandanaran.The purpose of this study is to describe and analyze the influence customer perceptions of the interest in using mobile banking. This research uses explanatory (explanation) with a quantitative approach, in which customers of Bank Rakyat Indonesia (BRI) branch Semarang Pandanaran as a population, whereas samples taken by 100 respondents were determined by specific criteria. Research results with the t test showed that the variable perceived of usefulness, perceived ease of use and security separately (partial) significantly affects the interest in using mobile banking. Test results also showed that the variables of perceived usefulness, perceived ease of use, and security jointly (simultaneously) significantly affects the interest in using mobile banking. The magnitude of the effect of variable perception of usefulness, perceived ease of use, and security against the interest in using mobile banking is equal to 76.5%, while the rest influenced by other variables that are not addressed in this study.